2017
DOI: 10.1038/s41598-017-16720-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 regulates Osteogenic Differentiation of Periodontal Ligament Stem Cells by targeting Smad5

Abstract: Human periodontal ligament stem cells (hPDLSCs) are mesenchymal stem cells (MSCs) derived from dental and craniofacial tissues that exhibit high potential for differentiation into osteoblasts. Recently, microRNAs (miRNAs) have been established to play important roles in MSC osteogenesis. In the current study, we report that miR-21 was down-regulated in osteogenically differentiated PDLSCs. Overexpression of miR-21 significantly inhibited osteogenesis of hPDLSC, whereas its inhibition demonstrated the opposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 36 publications
0
65
0
Order By: Relevance
“…Cell-aggregate lysates were extracted by lysing the cells in by Western and IP protein extraction reagent (Beyotime, China) with a protease inhibitor cocktail (Sigma, U.S.A.) for 5 min on ice, and then the concentration of total protein was determined with BCA protein assay (Keygen Biotech, China) following the manufacturer's recommended protocol [27]. After being heated for 5 min at 100 • C in a loading buffer, loaded 20 mg of each detected protein sample was separated by sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS/PAGE) and then was electro-transferred into polyvinylidenedifluoride (PVDF) membranes (Millipore, Billerica, MA, U.S.A.).…”
Section: Western Blotting Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-aggregate lysates were extracted by lysing the cells in by Western and IP protein extraction reagent (Beyotime, China) with a protease inhibitor cocktail (Sigma, U.S.A.) for 5 min on ice, and then the concentration of total protein was determined with BCA protein assay (Keygen Biotech, China) following the manufacturer's recommended protocol [27]. After being heated for 5 min at 100 • C in a loading buffer, loaded 20 mg of each detected protein sample was separated by sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS/PAGE) and then was electro-transferred into polyvinylidenedifluoride (PVDF) membranes (Millipore, Billerica, MA, U.S.A.).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…Bound primary antibodies were detected by incubating for 1 h with horseradish peroxidase-conjugated goat anti-mouse or anti-rabbit IgG (CWBio, China). The membranes was washed and developed using a ECL Reagent (Millipore, U.S.A.) following the manufacturer's recommended protocol [27], and were quantified using the Image-Quant software.…”
Section: Figure 5 Schematic Diagram Of the Mechanism Through E2a-p21mentioning
confidence: 99%
“…MiR‐21 was reported to stimulate osteoblastic differentiation of MSCs through the PI3K/β‐catenin pathway in human umbilical cord MSCs . Yet, in human periodontal ligament stem cells (hPDLSCs), decreased expression of miR‐21 was observed during osteogenesis . At this point, evidence from functional studies showed consistently a positive role of miR‐21 in osteoclastogenesis; however, its role in osteoblast differentiation remained controversial.…”
Section: Mirnas In Human Osteoporosis Studiesmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, single‐stranded, noncoding, endogenous RNAs that lead to ubiquitous regulation of gene expression posttranscriptionally by targeting 3′UTR of mRNAs . Biological and pathological processes controlled by them are cell proliferation, differentiation, growth, cell cycle, apoptosis, and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…3 MicroRNAs (miRNAs) are small, single-stranded, noncoding, endogenous RNAs that lead to ubiquitous regulation of gene expression posttranscriptionally by targeting 3 0 UTR of mRNAs. 4,5 Biological and pathological processes controlled by them are cell proliferation, differentiation, growth, cell cycle, apoptosis, and metabolism. Osteoblast differentiation and maturation are typically controlled by miRNAs, which play a role in upregulation and downregulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%